Inversion Analysis of Landslides with Dual Structure Based on Morgenstern-Price Method - HAN Yu; NIE Peng; ZHAN Jie; CHEN Siyao (Renmin Zhujiang)
Slope stability is important in the investigation and design of water conservancy and hydropower projects,which has a great impact on the safety and stability of projects.The simplified Bishop method was used to calculate the stability of the slope in the study area for the first time of slope treatment,and the parameters were obtained from field sampling and laboratory tests.After the implementation,the anti-slide pile still has large deformation.By analysis,it is concluded that the calculating model is improperly selected,and the mechanical parameters of rock and soil mass in a saturated state are overly large,which leads to the distortion of calculations.For the second treatment,the mechanical model was re-established,and the limit equilibrium theory based on the Morgenstern-Price method and the Autobank software developed by Hohai University were used to analyze the sensitivity of slope stability in the study area.The influence of the cohesion c and the internal friction angle φ on the safety factor was studied,and the mechanical parameter invasion of rock and soil mass was conducted to provide a basis for secondary landslide control.The monitoring results show that the second slope treatment measures are safe and feasible,which indicates that the physical and mechanical parameters obtained by inversion are reliable.The inversion analysis method can provide reference for the stability calculation of similar dual structure slope engineering.